Flexible electrode and preparation method thereof

Through multi-layer flexible electrode unit structure and UV light separation technology, the existing flexible electrodes have been solved, such as high stress and low reliability, achieving double-sided conduction and high flexibility, reducing design complexity and cost.

CN119700128APending Publication Date: 2025-03-28RES INST OF SOUTHEAST UNIV IN SUZHOU
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411911943.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing flexible electrodes have problems such as high stress, low reliability, single-sided conduction, high wiring difficulty and material safety need to be improved.

Method used

A multi-layer flexible electrode unit structure is adopted, including a support layer and an electrode layer. The support layer is provided with an array-distributed through holes on the surface, the electrode layer forms a grid-shaped groove, and the substrate is separated by irradiation from the bottom by UV light, and a flexible electrode with double-sided conduction is obtained.

Benefits of technology

Effectively release stress, enhance flexibility, avoid electrode damage, achieve double-sided conduction, improve flexibility and reliability, and reduce design complexity and cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119700128A_ABST
    Figure CN119700128A_ABST
Patent Text Reader

Abstract

The invention discloses a flexible electrode and a preparation method thereof, and the flexible electrode comprises a plurality of flexible electrode units, each flexible electrode unit comprises a supporting layer and an electrode layer, the surface of each supporting layer is provided with through holes I which are distributed in an array, and the electrode layers are arranged on the surfaces of the through holes I and the surfaces of the supporting layers and form latticed grooves; the positions of the through holes of the flexible electrode units are staggered. The preparation method comprises the following steps: forming a sacrificial layer on the surface of a substrate; forming a supporting layer on the surface of the sacrificial layer; photoetching, developing and curing the supporting layer, and forming a plurality of through holes I in the supporting layer; forming an electrode layer on the surface of the obtained object, and forming a through hole II in the electrode layer; processing the electrode layer to form a latticed groove; irradiating the substrate from the bottom by adopting UV light, decomposing the contact part of the sacrificial layer and the substrate, and separating the substrate; and a BOE solution is used for cleaning, and the residual sacrificial layer is removed. The grid-shaped grooves are formed in the electrode layer, stress release is facilitated, flexibility is enhanced, and damage is not prone to occurring.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an electrode and a manufacturing method thereof, in particular to a flexible electrode and a manufacturing method thereof. Background Art

[0002] In the early days of brain-computer interfaces, traditional hard electrodes such as silicon-based electrodes were used. After implantation in the human body, they may induce immune responses, lead to scar tissue accumulation, hinder signal transmission, and even cause electrode failure. Due to the softness of brain tissue, hard electrodes may cause damage to brain tissue during implantation, such as electrode displacement and brain tissue damage. The emergence of flexible electrodes has greatly improved the problems of traditional hard electrodes, but it has also inevitably introduced some new problems. For example, the ink using screen printing technology is usually a slurry solution made by dissolving conductive materials (such as C, Ag, Cu, etc.) in resin, but the resin solution will evaporate and may be slightly toxic. Inkjet printing technology requires the use of specific conductive polymer inks or other suitable materials, but the research and development and production of these materials may face certain challenges, such as limitations in cost, availability, and performance.

[0003] The existing electrode layer still has a lot of stress, low reliability, easy damage, can only be turned on on one side, high wiring difficulty, and the material safety of different printing methods in the preparation process needs further improvement. Summary of the invention

[0004] Purpose of the invention: In order to overcome the deficiencies of the prior art, an object of the present invention is to provide a flexible electrode. Another object of the present invention is to provide a method for preparing a flexible electrode.

[0005] Technical solution: A flexible electrode described in the present invention includes several groups of flexible electrode units, the flexible electrode units include a support layer and an electrode layer, an array of through holes are arranged on the surface of the support layer, the electrode layer is arranged on the through holes and the surface of the support layer to form grid-like grooves; the positions of the through holes of the several groups of flexible electrode units are staggered with each other.

[0006] Furthermore, the support layer is made of Su-8 glue, polyimide or polydimethylsiloxane, and has a thickness of 1 to 30 μm.

[0007] Furthermore, the thickness of the electrode layer is 0.2-2 μm.

[0008] Furthermore, the flexible electrode unit also includes a metal layer. The metal layer is arranged on the surface of the electrode layer. The metal layer is made of gold or platinum. The total thickness of the electrode layer and the metal layer is 0.5 to 10 μm.

[0009] A method for preparing a flexible electrode according to the present invention comprises the following steps:

[0010] Step 1, forming a sacrificial layer on the surface of the substrate;

[0011] Step 2, forming a support layer on the surface of the sacrificial layer;

[0012] Step 3, photolithography, development, and curing are performed on the support layer to form a plurality of through holes 1 on the support layer;

[0013] Step 4, forming an electrode layer on the surface of the product obtained in step 3, and forming a plurality of through holes 2 on the electrode layer;

[0014] Step 5, processing the electrode layer to form grid-shaped grooves;

[0015] Step 6, using UV light to irradiate the substrate from the bottom, the contact part between the sacrificial layer and the substrate is decomposed, and the substrate is separated;

[0016] Step seven, washing the product obtained in step six with a BOE solution to remove the remaining sacrificial layer, thereby obtaining a flexible electrode unit.

[0017] Furthermore, step 2 to step 5 are repeated multiple times, preferably 1 to 3 times, and finally the positions of the through holes 1 of the plurality of groups of flexible electrode units obtained are staggered.

[0018] Furthermore, the surface of the electrode layer obtained in step 4 is coated with photoresist, the photoresist above the second through hole is removed by photolithography, a metal layer is electroplated on the exposed electrode layer, excess photoresist is removed, and the electrode layer is processed to form a grid-like groove.

[0019] Furthermore, in step 1, the substrate is made of any one of sapphire and quartz glass. The sacrificial layer is made of SiNx, polycrystalline silicon or amorphous silicon, and has a thickness of 200-300 nm.

[0020] Furthermore, in step 6, the wavelength of the UV light is 193nm to 248nm, and the energy density is 0.1 to 1J / cm 2 .

[0021] Working principle: Taking the silicon nitride sacrificial layer as an example, when UV light is used to irradiate from the bottom of the substrate, the ultraviolet light can excite the electrons in the silicon nitride material, causing it to jump to the conduction band, resulting in a series of chemical reactions such as charge transfer and charge redistribution. These reactions are accompanied by the generation of heat, causing the part of the material in contact with the substrate of the silicon nitride sacrificial layer to decompose due to high temperature. Silicon nitride has a high absorption coefficient for UV light, and UV light is absorbed at a very shallow interface. At the same time, the thermal conductivity of silicon nitride material is relatively low, and heat will not be transferred to the supporting layer. This decomposition process will form an obvious peeling layer at the interface between the two, thereby achieving the separation of the silicon nitride sacrificial layer and the substrate.

[0022] Beneficial effects: Compared with the prior art, the present invention has the following significant features:

[0023] 1. The electrode layer forms a grid-like groove, which is conducive to effectively releasing stress and enhancing flexibility, preventing the electrode layer from breaking or damaging the human body when bent or twisted, and is not easily damaged;

[0024] 2. After removing the substrate, the double-sided conductive electrode is more flexible and can be applied to more scenarios. At the same time, it can reduce the design complexity and save costs when achieving the same function as the single-sided conductive electrode;

[0025] 3. Multiple through holes are provided. On the one hand, the through holes allow current to flow between different parts of the electrode, and also provide channels for electrolytes or other fluids. On the other hand, the increase of through holes disperses stress and makes the flexible electrode more flexible.

[0026] 4. The electrode layers can be stacked in multiple layers, and more complex flexible electrodes can be designed to meet the needs of special scenarios. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 is a schematic structural diagram of the product obtained in step S1 of Example 1 of the present invention;

[0028] Figure 2 is a schematic structural diagram of the product obtained in step S2 of Example 1 of the present invention;

[0029] Figure 3 is a schematic structural diagram of the product obtained in step S3 of Example 1 of the present invention;

[0030] Figure 4 is a schematic structural diagram of the product obtained in step S4 of Example 1 of the present invention;

[0031] Figure 5 is a schematic structural diagram of the product obtained in step S5 of Example 1 of the present invention;

[0032] Figure 6 is a schematic diagram of the structure after coating the second support layer 11 in step S6 of embodiment 1 of the present invention;

[0033] Figure 7 is a schematic diagram of the structure after photolithography and development in step S6 of embodiment 1 of the present invention;

[0034] Figure 8 is a schematic structural diagram of the product obtained in step S6 of Example 1 of the present invention;

[0035] Fig. 9 is a schematic diagram of the structure after photolithography etching in step S6 of embodiment 1 of the present invention;

[0036] Fig.10 is a schematic diagram of the structure of UV light irradiation in step S7 of embodiment 1 of the present invention;

[0037] Fig.11is a schematic structural diagram of the separation of the substrate 2 in step S7 of embodiment 1 of the present invention;

[0038] Fig.12 is a schematic structural diagram of the product obtained in step S8 of Example 1 of the present invention;

[0039] Fig.13 is a schematic diagram of the structure after spin coating the photoresist 4 in step S5 of embodiment 2 of the present invention;

[0040] Fig.14 is a schematic diagram of the structure after a portion of the photoresist 4 is photoetched away in step S5 of embodiment 2 of the present invention;

[0041] Fig.15 is a schematic structural diagram of the product obtained in step S6 of Example 2 of the present invention;

[0042] Fig.16 is a schematic structural diagram of the product obtained in step S7 of Example 2 of the present invention;

[0043] Fig.17 is a schematic structural diagram of the product obtained in step S8 of Example 2 of the present invention;

[0044] Fig.18 is a schematic structural diagram of the product obtained in step S10 of embodiment 2 of the present invention;

[0045] Fig.19 is a schematic diagram of the structure of UV light irradiation in step S11 of embodiment 2 of the present invention;

[0046] Fig. 20 is a schematic structural diagram of the separation of the substrate 2 in step S11 of embodiment 2 of the present invention;

[0047] Fig.21 is a schematic structural diagram of the product obtained in step S12 of embodiment 2 of the present invention;

[0048] Fig. 22 It is a top view of embodiment 2 of the present invention. DETAILED DESCRIPTION

[0049] Example 1

[0050] A method for preparing a flexible electrode comprises the following steps:

[0051] S1, such as Figure 1A transparent substrate 2 is provided, and the substrate 2 is cleaned with acetone / isopropanol / deionized water, and then the surface is blown dry. The substrate 2 is any material such as sapphire, quartz glass, etc. A sacrificial layer 3 is formed on the surface of the substrate 2 by plasma enhanced chemical vapor deposition (PECVD), and the material of the sacrificial layer 3 is a silicon nitride film (SiNx). During the deposition process, it is necessary to accurately control the deposition parameters, such as temperature, pressure, gas flow, etc., to obtain the desired silicon nitride film thickness and properties. During plasma enhanced chemical vapor deposition (PECVD), the deposition temperature is: 150°C to 350°C, preferably 300°C; deposition pressure: 100mTorr to 1000mTorr, preferably 300mTorr; gas configuration: silane (SiH4), gas flow rate 5sccm to 20sccm, preferably 10sccm; ammonia (NH3), gas flow rate 20sccm to 100sccm, preferably 50sccm; deposition rate: 20 nanometers per minute (nm / min) to 100 nanometers per minute (nm / min), preferably 50 nanometers per minute (nm / min); deposition thickness: 200nm to 300nm. PECVD can also be replaced by chemical vapor deposition (CVD) technology, such as atmospheric pressure chemical vapor deposition (APCVD) and low pressure chemical vapor deposition (LPCVD).

[0052] S2, such as Figure 2 , use an appropriate cleaning agent (such as deionized water, alcohol or other special cleaning agents) to thoroughly clean the surface of the sacrificial layer 3 to remove surface pollutants, grease and impurities. After cleaning, blow dry the surface with nitrogen or dry air to ensure that there is no residual moisture. On the prepared sacrificial layer 3, use a spin coater or other coating equipment to evenly coat the Su-8 glue to obtain a support layer 11. During the coating process, it is necessary to control the coating speed, the concentration of the glue solution and the coating time to ensure that the support layer 11 can be evenly and defect-freely covered on the sacrificial layer 3. Since the Su-8 glue has a high viscosity and a slow curing speed, a slower spin coating speed is required, and multiple coatings are required to achieve the required thickness of the support layer 11. Rotation speed: 1000 revolutions per minute (rpm) to 4000 revolutions per minute (rpm), preferably 3000 revolutions per minute (rpm); Glue coating time: 30s to 1min, preferably 30s; Support layer 11 thickness: 1μm to 10μm, preferably 5μm.

[0053] S3, such as Figure 3, use an ultraviolet photolithography machine or other photolithography equipment to align and expose the mask with a through-hole pattern to a sample coated with a support layer 11. During the exposure process, it is necessary to control the exposure time and intensity to ensure that the pattern can be clearly transferred to the support layer 11. Since Su-8 glue has a high sensitivity, a shorter exposure time and a lower exposure intensity are required. After the exposure is completed, an appropriate developer is used to remove the unexposed or underexposed part of the support layer. During the development process, it is necessary to control the development time and the concentration of the developer to ensure that the pattern can be completely retained on the support layer 11. Common developers for Su-8 glue include organic solvents. The development time needs to be adjusted according to the complexity of the pattern and the thickness of the support layer 11, generally about 5 minutes. During the development process, the developer needs to be continuously stirred to ensure uniform development and avoid defects such as blurring and deformation of the pattern. After development, a number of circular through holes 111 are formed on the support layer 11. The curing temperature and time need to be adjusted according to the material and thickness of the support layer 11. Su-8 glue usually requires a higher curing temperature and a longer curing time, with a curing temperature of 150-300°C and a curing time of 10-60 minutes. The curing temperature and time need to be adjusted according to the material and thickness of the support layer. For Su-8 glue, a higher curing temperature and a longer curing time are usually required.

[0054] S4, such as Figure 4 , high-energy particles (such as ions or electrons) are used to bombard the metal target material, so that metal atoms are sputtered from the surface of the target material and deposited on the support layer 11. The sputtering deposition rate is high, and a high-purity metal film can be deposited. In a vacuum chamber, a gold, platinum or precious metal alloy target material is used as a sputtering source. By introducing an inert gas (such as argon) and applying an electric field to ionize it to form a plasma, the ions in the plasma are accelerated by the electric field and collide with the surface of the target material, sputtering the metal atoms on the target material. These sputtered atoms are then deposited on the surface of the substrate. After a period of accumulation, a uniform, dense and chemically stable gold, platinum or precious metal alloy electrode layer 12 is finally formed on the result of step S3, and a number of through holes 121 are formed on the electrode layer 12. The thickness of the electrode layer 12 is: 0.2μm to 2μm, preferably 0.5μm.

[0055] S5, such as Figure 5 , the electrode layer 12 is photoetched to form grid-like grooves 13 .

[0056] S6, repeating steps S2 to S5, that is, coating the surface of the product obtained in step S5 with a second support layer 11 according to the same process as step S2, such as Figure 6 According to the same photolithography and development method as step S3, a plurality of circular through holes 111 are formed on the second support layer 11, as shown in FIG. Figure 7The second electrode layer 12 is deposited by the same sputtering method as step S4. Figure 8 The second electrode layer 12 is removed by photolithography in the same manner as step S5 to form a grid-like groove 13, as shown in FIG. Fig. 9 As shown, two groups of stacked flexible electrode units 1 are obtained, and the positions of the through holes 121 of different groups of flexible electrode units 1 are staggered, and the two electrode layers 12 are connected.

[0057] S7, such as Figures 10-11 , UV light is used to irradiate from the bottom of the substrate 2, and the heat causes the part of the material in contact with the silicon nitride sacrificial layer 3 and the substrate 2 to decompose, thereby forming a peeling layer at the interface, and the substrate 2 is separated. The peeling layer thickness is about 30 to 50nm. The UV light wavelength is 193nm to 248nm, preferably 193nm; the energy density is 0.1J / cm 2 ~1J / cm 2 , preferably 0.2 J / cm 2 .

[0058] S8, such as Fig.12 The product obtained in S7 is cleaned with a buffered oxide etching solution (BOE solution), the remaining sacrificial layer 3 is removed, and laser cutting is performed to obtain a flexible electrode with double-sided conduction.

[0059] The flexible electrode obtained in this embodiment includes several groups of flexible electrode units 1 including flexible electrode units 1 stacked up and down, and the through hole 121 of the upper flexible electrode unit 1 is staggered with the through hole 121 of the lower flexible electrode unit 1, which is convenient for processing. The flexible electrode unit 1 includes a support layer 11 and an electrode layer 12, and the surface of the support layer 11 is provided with an array of through holes 111, and the electrode layer 12 forms a grid-like groove 13 on the surface of the through hole 111 and the support layer 11.

[0060] Example 2

[0061] In order to further improve the connectivity and structural strength so that it is not easy to break, based on Example 1, this embodiment adds a metal layer 14 on the surface of each electrode layer 12 to thicken it.

[0062] A method for preparing a flexible electrode comprises the following steps:

[0063] S1. Provide a transparent substrate 2, clean the substrate 2 with acetone / isopropanol / deionized water, and then blow dry the surface. The substrate 2 is any material such as sapphire, quartz glass, etc. Plasma enhanced chemical vapor deposition (PECVD) is used to form a sacrificial layer 3 on the surface of the substrate 2. The material of the sacrificial layer 3 is a silicon nitride film (SiNx). During the deposition process, it is necessary to accurately control the deposition parameters, such as temperature, pressure, gas flow, etc., to obtain the desired silicon nitride film thickness and properties. During plasma enhanced chemical vapor deposition (PECVD), the deposition temperature is: 150°C to 350°C, preferably 300°C; deposition pressure: 100mTorr to 1000mTorr, preferably 300mTorr; gas configuration: silane (SiH4), gas flow rate 5sccm to 20sccm, preferably 10sccm; ammonia (NH3), gas flow rate 20sccm to 100sccm, preferably 50sccm; deposition rate: 20 nanometers per minute (nm / min) to 100 nanometers per minute (nm / min), preferably 50 nanometers per minute (nm / min); deposition thickness: 200nm to 300nm. PECVD can also be replaced by chemical vapor deposition (CVD) technology, such as atmospheric pressure chemical vapor deposition (APCVD) and low pressure chemical vapor deposition (LPCVD).

[0064] S2. Use an appropriate cleaning agent (such as deionized water, alcohol or other special cleaning agents) to thoroughly clean the surface of the sacrificial layer 3 to remove surface pollutants, grease and impurities. After cleaning, blow dry the surface with nitrogen or dry air to ensure that there is no residual moisture. On the prepared sacrificial layer 3, use a spin coater or other coating equipment to evenly coat the PI glue to obtain a supporting layer 11. During the coating process, it is necessary to control the coating speed, the concentration of the glue and the coating time to ensure that the supporting layer 11 can be evenly and defect-freely covered on the sacrificial layer 3. Rotation speed: 1000 revolutions per minute (rpm) to 4000 revolutions per minute (rpm), preferably 3000 revolutions per minute (rpm); Glue coating time: 30s to 1min, preferably 30s; Support layer 11 thickness: 1μm to 10μm, preferably 5μm.

[0065] S3. Use a UV photolithography machine or other photolithography equipment to align and expose the mask with a through-hole pattern to a sample coated with a support layer 11. During the exposure process, the exposure time and intensity need to be controlled to ensure that the pattern can be clearly transferred to the support layer 11. PI glue may have different sensitivities and need to be adjusted according to its specific material properties. After the exposure is completed, use an appropriate developer to remove the unexposed or underexposed part of the support layer 11. During the development process, it is necessary to control the development time and the concentration of the developer to ensure that the pattern can be completely retained on the support layer 11. The developer of PI glue is tetramethylammonium hydroxide (TMAH), and the development time is about 1 minute. During the development process, the developer needs to be constantly stirred to ensure uniform development and avoid defects such as blurring and deformation of the pattern. After development, a number of circular through holes 111 are formed on the support layer 11. The curing temperature and time need to be adjusted according to the material and thickness of the support layer 11. The curing temperature and time need to be adjusted according to the material and thickness of the support layer. The curing temperature is between 200 and 250°C, and the curing time is 10 to 50 minutes.

[0066] S4. Use high-energy particles (such as ions or electrons) to bombard the metal target material, so that the metal atoms are sputtered from the surface of the target material and deposited on the support layer 11. The sputtering deposition rate is high, and a high-purity metal film can be deposited. In a vacuum chamber, a gold, platinum or precious metal alloy target material is used as a sputtering source. By introducing an inert gas (such as argon) and applying an electric field to ionize it to form a plasma, the ions in the plasma are accelerated by the electric field and collide with the surface of the target material, sputtering the metal atoms on the target material. These sputtered atoms are then deposited on the surface of the substrate. After a period of accumulation, a uniform, dense and chemically stable gold, platinum or precious metal alloy electrode layer 12 is finally formed on the result of step S3, and a number of through holes 121 are formed on the electrode layer 12. The thickness of the electrode layer 12 is 0.2μm to 2μm, preferably 0.5μm.

[0067] S5, such as Fig.13 , a layer of photoresist 4 is spin-coated on the electrode layer 12, and the upper surface of the photoresist 4 is flush. The thickness and uniformity of the photoresist 4 must be controlled during the coating process to ensure the effect of subsequent exposure and development. Mask production, such as Fig.14 , the photoresist 4 above the second through hole 121 of the electrode layer 12 is removed by photolithography to expose the portion of the electrode layer 12 with the second through hole 121 .

[0068] S6, such as Fig.15, a metal layer 14 is deposited on the electrode layer 12 by an electrochemical method, and the height of the metal layer 14 does not exceed the height of the remaining photoresist 4. The surface of the metal layer 14 has a cylindrical through hole 141. Specifically: the result of step S5 is placed in an electroplating solution, and appropriate voltage and current are applied. The metal ions move toward the cathode support layer 11 under the action of the electric field and are reduced to metal atoms thereon. By controlling the electroplating time and current density, the thickness of the deposited layer can be precisely controlled. After the electrode layer 12 and the metal layer 14 are thickened, the total thickness is 0.5μm to 10μm.

[0069] S7, such as Fig.16 , reverse photolithography, remove excess photoresist 4.

[0070] S8, such as Fig.17 , use a chemical etching method to remove the excess metal layer 14 on the support layer 11, and process the electrode layer 12 to form a grid-like groove 13.

[0071] S9, then blow dry the sample with nitrogen or dry air. After the electrode layer 12 is thickened with the metal layer 14, on the one hand, it is not easy to break, and on the other hand, the connectivity of the through hole is enhanced.

[0072] S10, repeating steps S2 to S9, the support layer 11 and the metal layer 14 both have two layers, such as Fig.18 As shown, two groups of stacked flexible electrode units 1 are obtained, and the positions of the through holes 141 of different groups of flexible electrode units 1 are staggered, and the metal layer 14 of the next group is connected to the electrode layer 12 of the previous group.

[0073] S11, such as Figures 19-20 , UV light is used to irradiate from the bottom of the substrate 2, and the heat causes the part of the material in contact with the silicon nitride sacrificial layer 3 and the substrate 2 to decompose, thereby forming a peeling layer at the interface, and the substrate 2 is separated. The peeling layer thickness is about 30 to 50nm. The UV light wavelength is 193nm to 248nm, preferably 193nm; the energy density is 0.1J / cm 2 ~1J / cm 2 , preferably 0.2 J / cm 2 .

[0074] S12, such as Fig.21 The product obtained in S11 is cleaned with a buffered oxide etching solution (BOE solution), the remaining sacrificial layer 3 is removed, and laser cutting is performed to obtain a flexible electrode with double-sided conduction.

[0075] Although the sputtering process can form high-quality films, its deposition rate is relatively low, and it is difficult to directly form an electrode layer of sufficient thickness to meet certain application requirements. Therefore, it is not possible to sputter to form an electrode layer of target thickness in one go. The electroplating process has a high deposition rate and can quickly thicken the electrode layer. Electroplating can also provide a uniform coating, which helps to improve the surface quality and performance of the electrode. The electrode layer can provide good adhesion. As the bottom layer before electroplating, the electrode layer can enhance the adhesion between the metal layer and the support layer. This helps to prevent the metal layer from falling off or peeling off during subsequent use. The electrode layer can provide a uniform substrate so that the metal layer can maintain uniform thickness and morphology during the deposition process. This helps to improve the performance and reliability of the electrode. The method of forming an electrode layer by sputtering and then thickening the electrode layer by electroplating can flexibly adjust the composition and structure of the electrode. For example, different sputtering materials can be selected as the electrode layer to improve the performance of the metal layer or meet specific application requirements. Although sputtering and electroplating are both mature process methods, their costs are different. The method of forming a thinner electrode layer by sputtering and then thickening the electrode layer by electroplating can reduce material costs while ensuring electrode performance.

[0076] like Fig. 22 The flexible electrode obtained in this embodiment includes several groups of flexible electrode units 1 including flexible electrode units 1 stacked up and down, and the through hole three 141 of the upper flexible electrode unit 1 is staggered with the through hole three 141 of the lower flexible electrode unit 1, which is convenient for processing. The flexible electrode unit 1 includes a support layer 11, an electrode layer 12 and a metal layer 14, and an array of cylindrical through holes 111 is arranged on the surface of the support layer 11, and the electrode layer 12 forms a grid-like square groove 13 and a cylindrical through hole 121 on the surface of the support layer 11, and the surface of the metal layer 14 has a cylindrical through hole three 141.

[0077] Example 3

[0078] The remaining steps of this embodiment are the same as those of Embodiment 2, with the only difference being that the support layer 11 is made of polydimethylsiloxane (PDMS).

[0079] Accordingly, step S2 is replaced by: S2.1, cleaning the surface of the sacrificial layer 3: Use an appropriate cleaning agent (such as deionized water, alcohol or other special cleaning agents) to thoroughly clean the surface of the sacrificial layer 3 to remove surface pollutants, grease and impurities. After cleaning, blow dry the surface with nitrogen or dry air to ensure that there is no residual moisture. S2.2, preparation of PDMS support layer 11: Mix the PDMS prepolymer and the curing agent in a certain proportion to form a PDMS solution. Avoid introducing bubbles during the mixing process, and remove bubbles by vacuum degassing and other methods. Use a spin coater or other coating equipment to evenly coat the PDMS solution on the sacrificial layer 3. During the coating process, the coating speed, solution concentration and coating time need to be controlled to ensure that the PDMS layer can be evenly and defect-freely covered on the sacrificial layer 3. The thickness of the first support layer: 10μm to 100μm, preferably 20μm. Place the sample coated with the PDMS layer on a hot plate for curing. The curing temperature and time need to be adjusted according to the specific material and thickness of the PDMS to ensure that the PDMS layer is completely cured and has good mechanical properties. Since PDMS is not photosensitivity, electrode area patterns cannot be directly formed on it by conventional methods such as photolithography.

[0080] Step S3 is replaced by: using laser cutting equipment to accurately cut the PDMS layer according to the preset electrode through-hole pattern. Laser cutting has the advantages of high precision and high efficiency, which can ensure the accuracy and integrity of the electrode area and through-hole pattern. The side wall of the through-hole has a certain inclination to ensure the connectivity of the through-hole.

Claims

1. A flexible electrode, characterized in that: The invention comprises a plurality of groups of flexible electrode units (1), wherein the flexible electrode units (1) comprise a support layer (11) and an electrode layer (12), wherein the surface of the support layer (11) is provided with array-distributed through holes (111), and the electrode layer (12) is provided on the surface of the through holes (111) and the support layer (11) to form grid-shaped grooves (13); and the positions of the through holes (13) of the plurality of groups of flexible electrode units (1) are staggered with each other.

2. A flexible electrode according to claim 1, characterized in that: The support layer (11) is made of Su-8 glue, polyimide or polydimethylsiloxane and has a thickness of 1 to 30 μm.

3. A flexible electrode according to claim 1, characterized in that: The electrode layer (12) has a thickness of 0.2 to 2 μm.

4. A flexible electrode according to claim 1, characterized in that: The flexible electrode unit (1) further comprises a metal layer (14); the metal layer (14) is arranged on the surface of the electrode layer (12); the metal layer (14) is made of gold or platinum; and the total thickness of the electrode layer (12) and the metal layer (14) is 0.5 to 10 μm.

5. The method for preparing a flexible electrode according to claim 1, characterized in that: The following steps are involved: Step 1, forming a sacrificial layer (3) on the surface of the substrate (2); Step 2: forming a support layer (11) on the surface of the sacrificial layer (3); Step three, photolithography, development, and curing are performed on the support layer (11) to form a plurality of through holes (111) on the support layer (11); Step 4, forming an electrode layer (12) on the surface of the product obtained in step 3, and forming a plurality of through holes 2 (121) on the electrode layer (12); Step 5, processing the electrode layer (12) to form grid-shaped grooves (13); Step six, using UV light to irradiate the substrate (2) from the bottom, so that the contact portion of the sacrificial layer (3) with the substrate (2) is decomposed, and the substrate (2) is separated; Step 7: Wash the product obtained in step 6 with a BOE solution to remove the remaining sacrificial layer (3) to obtain a flexible electrode unit (1).

6. The method for preparing a flexible electrode according to claim 5, characterized in that: The steps 2 to 5 are repeated multiple times, and the positions of the through holes 1 (111) of the finally obtained groups of flexible electrode units (1) are staggered.

7. The method for preparing a flexible electrode according to claim 5, characterized in that: The surface of the electrode layer (12) obtained in step 4 is coated with a photoresist (4), the photoresist (4) above the second through hole (121) is removed by photolithography, a metal layer (14) is electroplated on the exposed electrode layer (12), excess photoresist (4) is removed, and the electrode layer (12) is processed to form a grid-shaped groove (13).

8. The method for preparing a flexible electrode according to claim 5, characterized in that: In the step 1, the substrate (2) is made of any one of sapphire and quartz glass.

9. The method for preparing a flexible electrode according to claim 5, characterized in that: In the step 1, the sacrificial layer (3) is made of SiNx, polycrystalline silicon or amorphous silicon and has a thickness of 200 to 300 nm.

10. The method for preparing a flexible electrode according to claim 5, characterized in that: In step 6, the wavelength of UV light is 193nm to 248nm, and the energy density is 0.1 to 1J / cm 2 .